About of Malgrange Theorem - Fernández Sánchez, Percy Braulio (2019)
In this article we will prove of Malgrange Theorem on a subﬁeld K of the complex numbers, this demonstration is due to Moussu. This result is important in the theory of foliations and shows that all holomorphic foliations of Codimension one with a small singular set has holomorphic ﬁrst integral.